WatsaQ: Repository of Al Hadith in Bahasa (Case Study: Hadith Bukhari) - Atqia Aulia; Dewi Khairani; Rizal Broer Bahaweres; Nashrul Hakiem (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
The Hadith is one of the two sources of Islamic law after the Qur'an. It is a fact that there are a number of false hadith, recognised by Muslim scholars since the end of the first century of Hijra, and even earlier. In addition to the breadth of false hadith circulating among the public at this  time,  it  is difficult to determine the source of authenticity and distinguish false  from genuine.  This  is  due  to  the  configuration of  the genuine documents which are revealed in Arabic. To that end, the  authors  have  built  a  repository  collection  of  hadith al- Bukhari in the Indonesian language. The hadith chosen have secured originality and standardisation has been applied that can assist users in learning the content of the hadith. The authors implemented a repository of translation in Bahasa of Bukhari Hadith using XML schema. To study the repository performance, we use a web presentation using PHP employing brute-force string match algorithms to display the search results based on keywords entered by the user. We analyse the results of our proposed repository implementation average searching time is faster by 0.85 milliseconds compared with the repository based on the unstructured one.